Mapping Global Governance of Antibiotic Stewardship: a One Health Multi-Level Governance Approach - Shedeed, Eyad (Université d'Ottawa | University of Ottawa, 2024)
This study embarks on a critical examination of antibiotic stewardship (ABS) across the interconnected domains of human, animal, and environmental health, in response to the growing challenge of antimicrobial resistance (AMR). Utilizing a scoping review format and including academic and grey literature, the research aims to dissect and evaluate the ABS policies implemented by both public and private sectors. The focus is on unearthing common strategies, identifying patterns, and highlighting disparities among diverse stakeholders within the One Health framework. The study's objective is to uncover effective governance mechanisms that promote ABS strategies that can significantly contribute to the global fight against AMR. By analyzing global governance mechanisms, this research further aspires to inform and enhance the One Health global governance framework. The expected outcome is a novel, comprehensive perspective on ABS, integrating a holistic and interdisciplinary approach that aligns with the multifaceted nature of AMR. This approach promises to yield insights that are vital for shaping future policies and actions in AMR mitigation.
Keywords: Antimicrobial Resistance; Antibiotic Stewardship; Global Governance